Pallidal Deep Brain Stimulation for Monogenic Dystonia: The Effect of Gene on Outcome - Tisch, Stephen; Kumar, Kishore Raj (Frontiers in Neurology, 2021)
Globus pallidus internus deep brain stimulation (GPi DBS) is the most effective intervention for medically refractory segmental and generalized dystonia in both children and adults. Predictive factors for the degree of improvement after GPi DBS include shorter disease duration and dystonia subtype with idiopathic isolated dystonia usually responding better than acquired combined dystonias. Other factors contributing to variability in outcome may include body distribution, pattern of dystonia and DBS related factors such as lead placement and stimulation parameters. The responsiveness to DBS appears to vary between different monogenic forms of dystonia, with some improving more than others. The first observation in this regard was reports of superior DBS outcomes in DYT-TOR1A (DYT1) dystonia, although other studies have found no difference. Recently a subgroup with young onset DYT-TOR1A, more rapid progression and secondary worsening after effective GPi DBS, has been described. Myoclonus dystonia due to DYT-SCGE (DYT11) usually responds well to GPi DBS. Good outcomes following GPi DBS have also been documented in X-linked dystonia Parkinsonism (DYT3). In contrast, poorer, more variable DBS outcomes have been reported in DYT-THAP1 (DYT6) including a recent larger series. The outcome of GPi DBS in other monogenic isolated and combined dystonias including DYT-GNAL (DYT25), DYT-KMT2B (DYT28), DYT-ATP1A3 (DYT12) and DYT-ANO3 (DYT24) have been reported with varying results in smaller numbers of patients. In this article the available evidence for long term GPi DBS outcome between different genetic dystonias is reviewed to reappraise popular perceptions of expected outcomes and revisit whether genetic diagnosis may assist in predicting DBS outcome.